Activity in the Ventral Medial Prefrontal Cortex Is Necessary for the Therapeutic Effects of Extinction in Rats - Fucich, Elizabeth A. (J Neurosci, 2018)
Poor response and high relapse rates remain problematic in the treatment of stress-related psychiatric disorders such as depression and post-traumatic stress disorder. Although mechanisms of pharmacotherapies are intensely studied, little is known about mechanisms of behavioral therapy that could inform improved treatments. We have previously demonstrated the therapeutic effects of extinction learning as a behavioral intervention modeling exposure therapy in rats. In the present study, we tested the hypothesis that activity in the ventral medial prefrontal cortex (vmPFC) during extinction is necessary for its therapeutic effects. The inhibitory Gi-coupled designer receptor exclusively activated by designer drug CaMKIIα-hM4Di was expressed in vmPFC before administering chronic unpredictable stress (CUS). vmPFC projection neurons were then inhibited during extinction treatment by administering clozapine-N-oxide. Coping behavior and cognitive flexibility were assessed 24 h later on the shock-probe defensive burying test and attentional set-shifting test, respectively. Replicating previous results, extinction reversed the CUS-induced deficits in coping behavior and cognitive flexibility. Inhibiting vmPFC during extinction blocked these therapeutic effects. Further, increasing vmPFC activity with the excitatory Gq-coupled designer receptor exclusively activated by designer drug hM3Dq 24 h before testing was sufficient to reverse the CUS-induced deficits. CUS reduced mPFC responsivity, assessed by measuring afferent-evoked field potentials in the mPFC, and this reduction was reversed by extinction treatment 24 h before testing. These results demonstrate the necessity of vmPFC activity in the therapeutic effects of extinction as a model of exposure therapy, and suggest that increased vmPFC activity induced by extinction is sufficient to produce lasting plastic changes that underlie its beneficial effects. SIGNIFICANCE STATEMENT Stress-related psychiatric disorders remain poorly treated. Psychotherapies can be effective, but their mechanisms remain unknown, hindering progress toward improved treatment. We used a rat model of behavioral therapy to identify potential targets for enhancing treatment. Fear extinction as a therapeutic behavioral intervention reversed stress-induced cognitive dysfunction and passive coping in rats, modeling components of stress-related psychiatric disease. Extinction also reversed stress-induced attenuation of mPFC responsivity. The therapeutic effects were prevented by blocking activity of glutamatergic neurons in the mPFC during extinction, and were mimicked by inducing activity in lieu of extinction. Thus, activity and plasticity in the mPFC underlie the beneficial effects of extinction on cognitive flexibility and coping behavior compromised by stress, and could be targets to enhance behavioral therapy.